2010
DOI: 10.1001/jama.2010.619
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Major Depressive Episodes in Patients With Chronic Kidney Disease and Initiation of Dialysis, Hospitalization, or Death

Abstract: Context Patients with chronic kidney disease (CKD) experience increased rates of hospitalization and death. Depressive disorders are associated with morbidity and mortality. Whether depression contributes to poor outcomes in patients with CKD not receiving dialysis is unknown. Objective To determine whether the presence of a current major depressive episode (MDE) is associated with poorer outcomes in patients with CKD. Design, Setting, and Patients Prospective cohort study of 267 consecutively recruited ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
187
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(210 citation statements)
references
References 43 publications
13
187
4
1
Order By: Relevance
“…45 The results of this study echoed another landmark study by Hedayati et al which found patients with both a CKD and a clinical diagnosis of depression twice more likely to be hospitalized and more than three times likely to progress to ESRD and dialysis than patients who are nondepressed. 46 This association was found to be independent …”
Section: Consequences Of Depression and Anxiety On Treatment Outcomesmentioning
confidence: 84%
“…45 The results of this study echoed another landmark study by Hedayati et al which found patients with both a CKD and a clinical diagnosis of depression twice more likely to be hospitalized and more than three times likely to progress to ESRD and dialysis than patients who are nondepressed. 46 This association was found to be independent …”
Section: Consequences Of Depression and Anxiety On Treatment Outcomesmentioning
confidence: 84%
“…The importance of providers' addressing mood disorders in patients with CKD as early as possible (16,30) and of dialysis facilities' screening for depression and managing mood disorders in their patients using strategies such as counseling and cognitive-behavioral therapy (15) is increasingly acknowledged. Wells et al (31) found in a randomized clinical trial that depressed patients who were identified in primary care practices had a higher chance of remaining employed for at least 1 year when they received treatment that addressed depression in a quality-improvement program, and these outcomes applied to patients with a 12-month or lifetime disorder as well as to patients with depressive symptoms only.…”
Section: Discussionmentioning
confidence: 99%
“…This is of great importance because the presence of depression in CKD is associated with poorer outcomes such as hospitalizations, progression to dialysis, and death (2,3). In spite of these grave outcomes, depression is often unrecognized, underdiagnosed, and undertreated (4,5) in these patients because CKD patients have somatic symptoms that can mimic symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%